Safety, efficacy, and patient acceptability of imiquimod for topical treatment of actinic keratoses - Caperton CV; Berman B (Dove Medical Press, 2011)
Caroline Caperton, Brian BermanDepartment of Dermatology and Cutaneous Surgery, Miller School of Medicine, University of Miami, Miami, FL, USAAbstract: Imiquimod, an immune-modulating imidazoquinoline compound, has been approved in topical formulation for the treatment of actinic keratoses, superficial basal cell carcinomas, and external genital warts. Its use in the treatment of field cancerization, in particular, has been rapidly evolving. With the recent approval of a new drug application for a new concentration, as well as generic formulations, this drug has emerged at the forefront of treatment for actinic keratoses, with improved dosage scheduling and more patients having access to generic options. In the nearly 15 years since its original approval by the Food and Drug Administration for the treatment of actinic keratoses in 1997, topical imiquimod has been reviewed and studied extensively, not only for its safety and efficacy, but also for its tolerability in patients. This paper provides an indepth review of the literature, and provides clinical evidence for its inclusion in the arsenal of treatment options for patients with actinic keratoses.Keywords: imiquimod, actinic keratoses, field cancerization, field therapy